THE RESPONSE OF DIFFERENT VARIETIES OF HORDEUM VULGARE L. CROP TO THE IRON FOLIAR NUTRITION (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
A field experiment was conducted during the 2022-2023 agricultural season to study the effect of foliar application of iron (0, 100, 200 ppm) on some growth traits, yield, and its components for five barley varieties (Sameer, Ebaa 99, Ebaa 256, Ebaa 249, Amal). The experiment was conducted using a randomized complete block design (RCBD), and treatments were distributed using a split-plot design with three replications. The iron concentrations were in the main plots, and the barley varieties were in the subplots. Iron was sprayed in two equal doses, the first at the tillering stage and the second at the elongation stage. The results indicated that the Ebaa 256 excelled in plant height, 1000-grain weight, and biological yield, while the Ebaa 249 outperformed in flag leaf area, number of tillers, number of spikes per square meter, spike length, and grain yield, which reached (4.82 tons. ha-1 The level 200 ppm recorded the highest values for most of the studied parameters, recording the highest grain yield of 4.57 tons. ha-1. However, iron had no significant effect on biological yield. Ebaa 256 at the 200-ppm level achieved the highest values in plant height, 1000-grain weight, and biological yield, while the Ebaa 249 at the 200 ppm level showed significant superiority in the remaining studied parameters, recording the highest averages and the highest yield of 4.99 ton. ha-1.